Surgical treatment of genital prolapse in combination with endometrial hyperplastic processes in postmenopausal women - Albina Kh. Karanasheva; Yulia E. Dobrokhotova; Svetlana A. Khlynova; Eleonora A. Markova; Regina M. Fuzailova (IP Berlin A.V., 2023)
Aim. To study the long-term results of surgical treatment of postmenopausal patients with genital prolapse III and IV according to the POP-Q classification in combination with endometrial hyperplastic processes and to assess their quality of life. Materials and methods. Fifty one elderly and senile patients with grade III-IV prolapse according to the POP-Q classification in combination with endometrial hyperplastic processes. 2 groups were formed: 1st - 21 patients after one-stage vaginal extirpation of the uterus with appendages and unilateral sacrospinous fixation of the vaginal stump with a synthetic endoprosthesis-tape in combination with reconstruction of II and III levels of pelvic floor support according to DeLancey; 2nd - 30 patients after one-stage vaginal extirpation of the uterus with appendages and median colporrhaphy using the Lefort and Neugebauer technique. Results. The study was evaluated 1-7 years after surgical treatment. The average age of patients at the time of surgery in group 1 was 63.12±4.32 years, in group 2 - 74.2±3.28 years. The number of women with somatic pathology in the 1st group was 1.7 times less in percentage terms than in the 2nd. The disappearance of symptoms of an overactive bladder after surgery was noted by 4 (50.0%) of 8 patients of the 1st group and 4 (26.7%) of 15 women of the 2nd. Uroflowmetry after surgical treatment showed an increase in the maximum flow rate (Qmax) and a decrease in the volume of residual urine (Vom) in both groups (p0.001). Recurrence of genital prolapse was detected in the apical region in 1 (4.8%) woman, prolapse of the anterior vaginal wall in 1 (4.8%). There were no recurrences of genital prolapse in the 2nd group. A significant improvement in the quality of life after surgery, according to the results of processing the PFDI-20 questionnaire, was noted by 19 (90.5%) women in the 1st group and 29 (96.7%) - in the 2nd. Conclusion. The long-term results of the proposed operational benefits have shown satisfactory results and can be successfully used in the elderly and senile age. The choice of the volume of surgery taking into account age, sexual activity, concomitant gynecological and somatic pathology reduces the number of complications and improves the results of surgical treatment in this category of patients.